ABCA1-dependent serum cholesterol efflux capacity inversely correlates with pulse wave velocity in healthy subjects - Favari, Elda (The American Society for Biochemistry and Molecular Biology, 2013)
The capacity of HDL to induce cell cholesterol efflux is considered one of its main antiatherogenic properties. Little is known about the impact of such HDL function on vascular physiology. We investigated the relationship between ABCA1-dependent serum cholesterol efflux capacity (CEC), an HDL functionality indicator, and pulse wave velocity (PWV), an indicator of arterial stiffness. Serum of 167 healthy subjects was used to conduct CEC measurement, and carotid-femoral PWV was measured with a high-fidelity tonometer. J774 macrophages, labeled with [(3)H]cholesterol and stimulated to express ABCA1, were exposed to sera; the difference between cholesterol efflux from stimulated and unstimulated cells provided specific ABCA1-mediated CEC. PWV is inversely correlated with ABCA1-dependent CEC (r = −0.183; P = 0.018). Moreover, controlling for age, sex, body mass index, mean arterial pressure, serum LDL, HDL-cholesterol, and fasting plasma glucose, PWV displays a significant negative regression on ABCA1-dependent CEC (β = −0.204; 95% confidence interval, −0.371 to −0.037). The finding that ABCA1-dependent CEC, but not serum HDL cholesterol level (r = −0.002; P = 0.985), is a significant predictor of PWV in healthy subjects points to the relevance of HDL function in vascular physiology and arterial stiffness prevention.